COMPLEX RADIONUCLIDE EVALUATION OF STRUCTURAL AND FUNCTIONAL KIDNEY`S DISORDERS OF CHILDREN WITH ACUTE PYELONEPHRITIS IN THE DYNAMIC OF PATHOLOGY PROCESS - Kundin, V. U. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Children`s acute pyelonephritis (APN) is the most important and difficult among microbes-inflammatory kidney`s deceases. Kidney`s APN functional disorders are evaluated generally by clinical and laboratory criteria which not always have high informativity. Scintigraphic kidney`s examinations with nephrothropic radiopharmaceuticals (NRP) are more informative. Materials and methods. 93 children (range 5-16 years) with APN were examined with different NRP. 45 from them were in acute stage of disease and 48 in remission. Scintigraphic examinations were being made on gamma-camera «SPECT-1» with using of NRP 99mTc-DTPA, 99mTc-pyrophosphate, 99mTc-MAG3, 99mTc-EC, 99mTc-DMSA. Results. Hemodynamic changes in APN are presented signs of the venous stagnation by parenchyma. Retention of NRP in the kidney`s parenchyma and deceleration of excretory processes testify about the main process in parenchyma. Kidney`s filtration disorders have all patients in all stages of APN with disorders of both kidneys. 40,8% patients have inflammation sites in the kidneys parenchyma. Conclusion. The most informative are 99mTc-DTPA and 99mTc-pyrophosphate for initial examinations, 99mTc-MAG3 and 99mTc-DMSA for monitoring examinations.